Analisis Faktor Yang Mempengaruhi Perilaku Santri Dalam Menjaga Kebersihan Lingkungan - Yulia Putri Fatmilarini; Shinta Wahyusari; Ainul Yaqin Salam (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Clean and Healthy Living Behavior (PHBS) is a behavior that is practiced by every individual with their own awareness to improve their health and play an active role in creating a healthy environment. The purpose of this study is to identify the variabels that influence environmental cleanliness behavior.. This research method uses correlational analytic with cross sectional approach. The sampling technique used is stratified random sampling on the respondents with a total sample of 178 respondents. According to the study’s findings all the components werwrelated with a p value of 0,05, including knowledge, attitudes, facilities, and the role administrators, while the dominant factor related to the behavior of students in maintaining a clean environment with a p value of 0.001 0.05 and OR value = 5.269. can be concluded that knowledge, attitudes, facilities, the role of the board can influence behavior but the most dominant factor in behavior is the role of the board, so that future researchers are expected to provide intervention to administrators and students regarding the importance of keeping the environment clean.